A Role of Suppressor of Cytokine Signaling 2 in the Regulation of Ecdysteroid Signaling Pathway in Procambarus clarkii. Issue 7 (27th July 2016) - Zhu, Baojian; Dai, Lishang; Yu, Yingying; Wang, Daojun; Peng, Tao; Liu, Chaoliang
ABSTRACT: A suppressor of cytokine signaling 2 (SOCS‐2) homolog was identified from the red crayfish Procambarus clarkii . Phylogenic analysis showed that P. clarkii SOCS‐2 (Pc‐SOCS‐2) was very similar to that of invertebrates. The sequence contains a central SH2 domain, a conserved SOCS box, and a variable N‐terminal domain. Real‐time polymerase chain reaction showed that Pc‐SOCS‐2 mRNA level was higher in muscle and heart than in the other tissues examined. A 40‐kDa recombinant protein was successfully expressed and purified from Escherichia coli cells as confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) and Western blotting. Pc‐SOCS‐2 was significantly downregulated in the hepatopancreas after 20‐hydroxyecdysone injection. Knockdown of Pc‐SOCS‐2 gene by small interfering RNA transfection in the hepatopancreas increased the expression levels of 20‐hydroxyecdysone‐responsive genes at 48 hr. Taken together, these results suggest that Pc‐SOCS‐2 is a negative regulator of ecdysteroid signaling transduction.